Internalizing Islamic Values through a Student Spirituality Club in an Indonesian Islamic Junior Secondary School - Mubarok, M Naelul; Alwi, Wildan; Al Mubarok, Moh Safik; Lutfiani, Nanin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This qualitative descriptive case study examines how Islamic values were internalized through an Islamic spirituality extracurricular club (Rohani Islam [Rohis]) to support student behavior formation at an Indonesian Islamic junior secondary school (Madrasah Tsanawiyah [MTs]). The available research record identifies the Rohis advisor, student members, and an Islamic Religious Education teacher as purposively selected informants. Data were generated through participatory observation, in-depth interviews, and documentation and analyzed through data condensation, data display, and conclusion drawing, with source and method triangulation supporting trustworthiness. The findings indicate that internalization operated through value transformation, value transaction, and transinternalization, enacted through knowledge-oriented instruction (ta'lim), holistic nurturing and guided practice (tarbiyah), and the cultivation of ethical conduct (ta'dib). The program combined new-student welcoming, competitions, and Qur'an reading courses with basic leadership training, a supervised overnight spiritual retreat (mabit), and structured dialogic discussion (mujadalah). It emphasized foundational Islamic belief (aqidah), worship practice (ibadah), and moral conduct (akhlaq). Implementation was supported by educator example, relational teacher approaches, student interest, and facilities, while uneven prior religious knowledge constrained participation. The study contributes an integrated process-program-condition framework without claiming causal behavioral change.